2001
DOI: 10.21273/jashs.126.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Chlorophyll Fluorescence as a Heat Stress Indicator in Tomato: Laboratory and Greenhouse Comparisons

Abstract: Chlorophyll fluorescence was measured under both laboratory and greenhouse conditions in an effort to develop a quick, reliable, and inexpensive laboratory procedure capable of predicting heat stress experienced by tomato (Lycopersicon esculentum Mill.) under greenhouse conditions. The laboratory tests consisted of measurements of the ratio of variable to maximal chlorophyll fluorescence (Fv/Fm) performed on leaf discs taken from whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…The ratio between variable fluorescence (F v = F m À F o ) and maximum fluorescence (F m ) or the maximum potential quantum efficiency of PSII (F v /F m ) provides an estimate of the maximum quantum efficiency of PSII (Butler, 1978), which is one of the most heat-affected fluorescence parameters. A decrease in F v / F m is frequently observed, when plants are subjected to abiotic stresses, including heat stress (Willits and Peet, 2001;MolinaBravo et al, 2011;Sharma et al, 2012). The reason for the stressinduced reduction in F v /F m is an increase in non-photochemical quenching processes leading to a decrease in F m and subsequent photoinactivation of PSII reaction centers, leading to an increase in F o (Melis, 1999;Baker, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio between variable fluorescence (F v = F m À F o ) and maximum fluorescence (F m ) or the maximum potential quantum efficiency of PSII (F v /F m ) provides an estimate of the maximum quantum efficiency of PSII (Butler, 1978), which is one of the most heat-affected fluorescence parameters. A decrease in F v / F m is frequently observed, when plants are subjected to abiotic stresses, including heat stress (Willits and Peet, 2001;MolinaBravo et al, 2011;Sharma et al, 2012). The reason for the stressinduced reduction in F v /F m is an increase in non-photochemical quenching processes leading to a decrease in F m and subsequent photoinactivation of PSII reaction centers, leading to an increase in F o (Melis, 1999;Baker, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chl fluorescence provides a non-destructive, rapid means of assessing both photo-chemical quantum yield and photoinhibition (Krause 1988, Krause andWeis 1991), and has been widely employed as an indicator of plant response to stresses, especially those imposed by air and water pollution (Lichtenthaler 1988), water deficit (Cornic and Massacci 1996), high and low temperature (Kristjansdottir andMerker 1993, Willits andPeet 2001), and salinity (Smillie and Nott 1982). Larcher (1994) has suggested that it may represent the most reliable way of quantifying photosynthesis in heat-stressed plants.…”
Section: Introductionmentioning
confidence: 99%
“…The Fv/Fm is an index of the maximum quantum yield of PSII photochemistry (Baker, 2008). Measurements of the Fv/Fm have been used in many studies to evaluate physiological activity, particularly a life activity, of fresh agricultural products during the growing period because these tests are rapid and nondestructive (Walker et al, 1990;Krause and Weis, 1991;Willits and Peet, 2001;Rizza et al, 2001;Kocheva et al, 2004). However, these measurements of physiological activity have not been applied in the processing of agricultural products to evaluate drying characteristics of samples.…”
Section: Introductionmentioning
confidence: 99%